2004
DOI: 10.1104/pp.103.033696
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Gibberellin Metabolism Enzyme Genes and Their Related Mutants in Rice  

Abstract: To enhance our understanding of GA metabolism in rice (Oryza sativa), we intensively screened and identified 29 candidate genes encoding the following GA metabolic enzymes using all available rice DNA databases: ent-copalyl diphosphate synthase (CPS), ent-kaurene synthase (KS), ent-kaurene oxidase (KO), ent-kaurenoic acid oxidase (KAO), GA 20-oxidase (GA20ox), GA 3-oxidase (GA3ox), and GA 2-oxidase (GA2ox). In contrast to the Arabidopsis genome, multiple CPS-like, KS-like, and KO-like genes were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
659
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(693 citation statements)
references
References 33 publications
27
659
0
7
Order By: Relevance
“…3B). The induction of OsKS8 (OsDTC2) mRNA by UV irradiation was also reported by Sakamoto et al [21] quite recently. GC-MS analysis indicated that the production of stemar-13-ene was induced in the rice leaves after UV irradiation (Fig.…”
Section: Expression Levels Of Osdtc2 Mrnamentioning
confidence: 79%
See 2 more Smart Citations
“…3B). The induction of OsKS8 (OsDTC2) mRNA by UV irradiation was also reported by Sakamoto et al [21] quite recently. GC-MS analysis indicated that the production of stemar-13-ene was induced in the rice leaves after UV irradiation (Fig.…”
Section: Expression Levels Of Osdtc2 Mrnamentioning
confidence: 79%
“…It is thus suggested that OsDTC2 is localized in plastids, as are OsDTC1 (ent-cassa-12,15-diene synthase) [12] and other plant diterpene cyclases such as ent-CPS and ent-kaurene synthase (ent-KS) [19,20]. Quite recently, it was suggested that several diterpene cyclase genes found in the rice genome are involved in the phytoalexin biosynthesis in rice [21], one of them tentatively named OsKS8 being identical to OsDTC2. However, functional analysis of OsKS8 has not been carried out.…”
Section: Gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Many GA-related mutants have been isolated from the model plant species Arabidopsis thaliana and rice (Oryza sativa L.), and the majority of the underlying genes have been found to encode enzymes that are related to GA metabolism or components of GA signaling [1][2][3][4][5][6][7]. Many GA mutants show dramatically reduced plant height and hence increased yield potential and lodging resistance of modern cereal varieties, thus greatly contributing to the success of the 'green revolution' [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a report on rice gibberellin metabolism, these regions had been previously noted to also contain genes encoding a number of CYPs, as well as short-chain alcohol dehydrogenases (Sakamoto et al, 2004). Many of these genes were found to be coregulated, specifically inducible by the fungal cell wall component chitin, as well .…”
Section: Investigation Of Rice Cyps In E Coli: Enabled By Gene Synthmentioning
confidence: 99%